Azide–alkyne cycloaddition (click) reaction in biomass-derived solvent CyreneTM under one-pot conditions - Zoltán Medgyesi; László T. Mika (Beilstein Journal of Organic Chemistry, 2025)
It was demonstrated that CyreneTM, as a biomass-originated polar aprotic solvent, could be utilized as an alternative reaction medium for one-pot copper(I)-catalyzed azide–alkyne cycloaddition (click or CuAAC) reactions, for the synthesis of various 1,2,3-triazoles under mild conditions. Nineteen products involving N-substituted-4-phenyl-1H-1,2,3- and 1-allyl-4-substituted-1H-1,2,3-triazoles were synthesized under one-pot conditions and isolated with good to excellent yields (50–96%) and purity (>98%). The observed results represent an example that proves that biomass-derived safer solvents can be introduced into a synthetically important transformation exhibiting higher chemical and environmental safety.